Caregivers' perspectives on the contextual influences within family management for ethnically diverse children with ADHD. Issue 2 (27th December 2021) - Paidipati, Cynthia P.; Deatrick, Janet A.; Eiraldi, Ricardo B.; Ulrich, Connie M.; Lane, Jamil M.; Brawner, Bridgette M.
Abstract: Purpose: Attention deficit hyperactivity disorder (ADHD) is a common neurodevelopmental disorder affecting over 9% of children in the United States. Family caregivers are often responsible for the management of their child's ADHD. Contextual influences, such as healthcare providers, systems, and resources, are factors contributing to the ease or difficulty of family management. The purpose of this article is to qualitatively describe the major contextual influences that impact family management for ethnically diverse children with ADHD. Design And Methods: This analysis is part of a mixed methods study using a concurrent nested design (QUAL + quant) to understand the phenomenon of family management from a contextual and socioecological perspective. In this analysis, cross‐sectional data from caregivers of children with ADHD ( N = 50) within a large northeastern city in the United States were collected, analyzed, and interpreted in the qualitative descriptive tradition. Semistructured interviews were conducted with participants to understand the contextual influences within family management. Conventional content analysis resulted in the emergence of barrier and facilitator domains and subdomains. Results: Caregivers were predominantly female (98%) and between 24 and 61 years with a mean age of 37.54 (SD = 1.18). Caregivers identified their children as Black or African American (56%), White (26%), Multi‐Racial (16%), Hispanic or Latinx (8%), and Asian (2%). Contextual influences within family management emerged as barrier or facilitator domains. Barrier domains included: (1) family, (2) healthcare systems, (3) educational systems, (4) stigma, and (5) financial, insurance, and policy issues. Facilitator domains included: (1) family and community, (2) healthcare providers, and (3) educational providers. Subdomains within each domain are expanded in the article. Practice Implications: Specialists in pediatric nursing should consider contextual influences within family management for ethnically diverse children with ADHD. As healthcare providers, it is important to recognize system‐level barriers or facilitators for caregivers and their children and find creative ways to overcome obstacles and leverage strengths within families, communities, and care systems. Another important area for pediatric specialists to consider is understanding how stigma impacts children with ADHD. Policy‐level engagement and advocacy should maximize the political will of nurses, families, and educators to create change within communities.